Safety and Efficacy of Brachytherapy in Inoperable Endometrial Cancer - Merten, Ricarda; Strnad, Vratislav; Schweizer, Claudia; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Schubert, Philipp; Karius, Andre; Schubert, Philipp (Journal of Personalized Medicine, 2024)
Background/Objectives: Radiotherapy represents the only treatment option for patients with inoperable endometrial cancer (EC). The aim of our study was to evaluate the efficacy and safety of brachytherapy (BT) in this selected patient population. Methods: Between 1990 and 2019, 18 patients with inoperable EC in stage FIGO I–IV were treated with intracavitary brachytherapy using the “Heyman Packing technique”. BT was performed either as sole PDR- or HDR-brachytherapy with a median cumulative dose up to 60.0 Gy (67.9 Gy EQD2 α/β = 3Gy) and 34.0 Gy (75.6 Gy EQD2 α/β = 3Gy), respectively. Results: The median follow-up was 46 months (6–219). The mean age was 71 years. The 5-year cumulative local recurrence rate (CLRR) for the whole cohort was 27.3%. The 5-year overall survival (OS), distant metastasis-free survival (DMFS), and disease-free survival (DFS) were 51%, 79%, and 69%. The 5-year DFS for low-, intermediate-, and high-risk EC was 89%, 50%, and 44% (p = 0.51). No significant difference in DFS was observed in patients over 70 (p = 0.526). No late side effects of grade > 1 were documented. Conclusions: Brachytherapy for inoperable EC is a safe and effective treatment option, offering good local control and OS with minimal toxicity. Moreover, brachytherapy effectively controls hemoglobin-relevant bleeding. Therefore, BT should be considered a viable alternative to non-curative treatment strategies in gynecological multidisciplinary conferences.
CRIS-Team Scopus Importer:2025-02-04
Keywords: brachytherapy; definitive treatment; endometrial cancer; hemostyptic irradiation; inoperable